Faktor-Faktor yang Berhubungan dengan Hipertensi Pada Lansia di Atas Umur 65 Tahun - Sri Agustina; Siska Mayang Sari; Reni savita (Jurnal Kesehatan Komunitas, 2014)
Aging process was an natural process which occured any changes at all body system of elderly, included cardiovascular system in which followed by main deseases were hypertension. The aim of this research was determined the factors related with hypertension on the elderly over 65 years. The data was collected on 87 elderly over 65 years old with hypertension whithin total sampling and also Fisher test as alternative test in factor heredity and obesity. The result showed there were relationship between heredity and hypertension with p value â‰¤ 0,05. There was no relationship between gender, obesity, smoking, stress, sport and hypertension with p value > 0,05. Recomended to elderly over 65 years old with hypertension to did routine blood pressure control and health officer should to promote health education about prevention of hypertension in elderly